Integrating Islamic Values in Maritime Education: Enhancing Humility, Responsibility, and Intercultural Competence - Faozun, Irfan; Sumali, Bambang; Kurniadi, Bambang; Utama, Yusuf Pria (Universitas Islam Negeri Raden Intan Lampung, 2025)
The maritime industry requires professionals who possess not only technical expertise but also strong ethical foundations and intercultural competence. This study offers a unique contribution by integrating Islamic values, such as humility, responsibility, and intercultural competence, into maritime cadet education, an area that remains underexplored in previous research. Unlike existing studies that primarily focus on technical or multicultural training, this research emphasizes character formation through religious and value-based education, aligning with the ethical demands of global maritime practice. This study aims to evaluate the extent to which Islamic values are embedded in cadet training programs, assess their effectiveness in shaping professional competencies, and recommend strategies for curriculum improvement. A qualitative research design was employed, involving semi-structured interviews and surveys with 20 stakeholders, including maritime professionals, lecturers, and recent graduates from Indonesian maritime institutions. Thematic analysis was used to categorize findings under the three core values. Data reliability was ensured through triangulation, expert validation of instruments, and cross-group comparison. The results reveal strong integration of Islamic values, with responsibility receiving the highest ratings, followed by humility and intercultural competence. While graduates confirmed the relevance of values in real-world settings, gaps were noted in experiential and intercultural training. The study highlights the strategic importance of values-based education in developing ethically grounded and globally competent seafarers. Recommendations include strengthening experiential learning, expanding multicultural exposure, and aligning curriculum with both industry standards and Islamic ethical principles.